Impact Evaluation of Free-of-charge CFL Bulb Distribution in Ethiopia - Costolanski, Peter (World Bank, Washington, DC, 2013)
Electricity infrastructure is one of the most important development challenges in Africa. While more resources are clearly needed to invest in new capacities, it is also important to promote energy efficiency and manage the increasing demand for power. This paper evaluates one of the recent energy-efficiency programs in Ethiopia, which distributed 350,000 compact fluorescent lamp bulbs free of charge. The impact related to this first phase is estimated at about 45 to 50 kilowatt hours per customer per month, or about 13.3 megawatts of energy savings in total. The overall impact of the compact fluorescent lamp bulb programs, thanks to which more than 5 million bulbs were distributed, could be significantly larger. The paper also finds that the majority of the program beneficiaries were low-volume customers -- mostly from among the poor -- although the program was not targeted. In addition, the analysis determines the distributional effect of the program: the energy savings relative to the underlying energy consumption were larger for the poor. The evidence also supports a rebound effect. About 20 percent of the initial energy savings disappeared within 18 months of the program's completion.